Iron-mineral accretion from acid mine drainage and its application in passive treatment*. Issue 11 (2nd June 2016) - Florence, K.; Sapsford, D.J.; Johnson, D.B.; Kay, C.M.; Wolkersdorfer, C.
ABSTRACT: This study demonstrates substantial removal of iron (Fe) from acid mine drainage (pH ≈3) in a passive vertical flow reactor (VFR) with an equivalent footprint of 154 m 2 per L/s mine water and residence times of >23 h. Average Fe removal rate was 67% with a high of 85% over the 10-month trial. The fraction of Fe passing a 0.22 µm filter (referred to here as Fe-filt) was seen to be removed in the VFR even when Fe(II) was absent, indicating that the contribution of microbial Fe(II) oxidation and precipitation was not the dominant removal mechanism in the VFR. Removal rates of Fe-filt in the VFR were up to 70% in residence times as low as 8 h compared with laboratory experiments where much smaller changes in Fe-filt were observed over 60 h. Centrifugation indicated that 80–90% of the influent Fe had particle sizes <35 nm. Together with analyses and geochemical modelling, this suggests that the Fe-filt fraction exists as either truly aqueous (but oversaturated) Fe(III) or nanoparticulate Fe(III) and that this metastability persists. When the water was contacted with VFR sludge, the Fe-filt fraction was destabilized, leading to an appreciably higher removal of this fraction. Heterogeneous precipitation and/or aggregation of nanoparticulate Fe(III) precipitates are considered predominant removal mechanisms. Microbial analyses of the mine water revealed the abundance of extracellular polymeric substance-generating Fe-oxidizing bacterium ' Ferrovum myxofaciens ', which may aid the removal of iron and explain the unusual appearance and physical properties of the sludge.